Molecular detection and Frequency of Fluoroquinolone-Resistant Escherichia coli by Multiplex Allele Specific Polymerase Chain Reaction (MAS-PCR). Issue 1 (1st January 2020) - Abou El-Khier, Noha Tharwat; Zaki, Maysaa El Sayed
ABSTRACT: The purpose of this study is to detect the frequency of fluoroquinolone-resistant Escherichia  coli (E. coli) clinical isolates from hospital-acquired infection (HAI) compared to community-acquired infection (CAI) by multiplex allele-specific polymerase chain reaction (MAS-PCR) for gyrA (at Ser-83 and Asp-87) and parC (at Ser-80 and Glu-84) mutations. Two hundred nonduplicate isolates of E. coli (100 from HAIs, 100 from CAIs) were collected. Antibiotics susceptibility was performed by MIC for ciprofloxacin. Mutations at gyrA and parC were determined by MAS-PCR. MICs of ciprofloxacin had significantly higher resistance pattern ≥4 μg/mL in E. coli isolated from HAIs (40%) compared to CAIs (28%) and intermediate levels of resistance in HAIs compared to CAIs (17% & 11%). The most frequent mutations were in gyrA 83 (29.5%), followed by gyrA 87 (20.5%). Par C mutations were less common with parC 80 (17.5%) and parC 84 (5%). The present study highlights the rise of resistance to fluoroquinolones amongst clinical isolates of E. coli that was significantly greater amongst isolates from HAIs than those isolates from CAIs. The mutations of resistant E. coli strains were more frequent in gyrA gene than parC gene. The study indicates the prominence of adherence to infection control guidelines and antibiotics policy.